Associação entre o risco de queda e o medo de cair em idosos atendidos na Estratégia Saúde da Família - Sousa Neto, Raimundo de Assunção (2017)
The general objective of the research was to verify the association of the risk of falling to the fear of falling in the elderly served in the Family Health Strategy of São Luís, Maranhão. The specific objectives were: To characterize the sociodemographic and health profile of elderly people more susceptible to falls; To verify the factors influencing the risk of falls in the elderly served in the Family Health Strategy; To verify the influencing factors in the fear of falling from the elderly served in the Family Health Strategy. This was a cross-sectional, analytical study with a quantitative approach carried out at the Basic Health Units of the city of São Luís, between September and November 2015, with elderly individuals aged 60 years or older, reaching a total of 203 researched. A sociodemographic and health identification card, Downton risk scale and fall efficacy scale were used as instruments of the research. Initially, the descriptive analysis was performed by means of absolute and relative frequencies. The chi-square association test was then used to evaluate the relationship between the risk of falling and fear of falling, and their relationship with sociodemographic characteristics. For significant associations, logistic regressions were calculated. The collected data was stored in a specific database created on the Microsoft Excel version 2016 spreadsheet. After that, the statistical analysis of the data was performed in the IBM SPSS program. The research is part of the project "Chronic Conditions in the Elderly Served in the Family Health Strategy in São Luís-MA", meets the aspects recommended in resolution 466/12, and was approved with the opinion number 949.100. The sample studied is mostly composed of women, aged 60-69 years, married, with at least complete primary education, who do not live alone, do not have a diagnosis of osteoporosis, have already received guidance on falls prevention, which Do not practice physical activity and when they do it, they do it in the same age group, until they are 89 years old and they have already diagnosed basic diseases. From the Chi-Square test a highly significant p-value was obtained, demonstrating that the risk of falling depends on the fear of falling. The characteristics of age, schooling, diagnosis of osteoporosis, not practicing physical activity and presenting underlying disease influence the risk of falling and fear of falling, since they present p-value with high significance, just as the fact of living alone also influences the Fear of falling. It is concluded that the risk of falling is associated with the fear of falling, that they are influenced by age, schooling, diagnoses of underlying diseases or osteoporosis, and sedentary lifestyle. It is assumed a high risk of falling into it.